Highly conserved Z and molecularly diverged W chromosomes in the fish genus Triportheus (Characiformes, Triportheidae) - Yano, C F; Bertollo, L A C; Ezaz, T; Trifonov, V; Sember, A; Liehr, T; Cioffi, M B (Heredity, 2017)
The main objectives of this study were to test: (1) whether the W-chromosome differentiation matches to species' evolutionary divergence (phylogenetic concordance) and (2) whether sex chromosomes share a common ancestor within a congeneric group. The monophyletic genus Triportheus (Characiformes, Triportheidae) was the model group for this study. All species in this genus so far analyzed have ZW sex chromosome system, where the Z is always the largest chromosome of the karyotype, whereas the W chromosome is highly variable ranging from almost homomorphic to highly heteromorphic. We applied conventional and molecular cytogenetic approaches including C-banding, ribosomal DNA mapping, comparative genomic hybridization (CGH) and cross-species whole chromosome painting (WCP) to test our questions. We developed Z- and W-chromosome paints from T. auritus for cross-species WCP and performed CGH in a representative species (T. signatus) to decipher level of homologies and rates of differentiation of W chromosomes. Our study revealed that the ZW sex chromosome system had a common origin, showing highly conserved Z chromosomes and remarkably divergent W chromosomes. Notably, the W chromosomes have evolved to different shapes and sequence contents within ~15-25 Myr of divergence time. Such differentiation highlights a dynamic process of W-chromosome evolution within congeneric species of Triportheus.
Keywords: Animals; srovnávací genomová hybridizace; ribozomální DNA; Female; biologická evoluce; DNA, Ribosomal; ženské pohlaví; mapování chromozomů; druhová specificita; Chromosome Mapping; malování chromozomů; Chromosome Painting; heterochromatin; Heterochromatin; Species Specificity; Phylogeny; pohlavní chromozomy; Male; Sex Chromosomes; Characidae; Comparative Genomic Hybridization; zvířata; mužské pohlaví; Biological Evolution; fylogeneze